Legal basis for the development of the Slovenian health system - from the enlightenment to the second world war - Pivec, Gregor (Acta Medico-Biotechnica, 2021)
Throughout the history of medicine, patient-doctor relationships remained intimate and were based on the patient’s expectations, which were more or less limited by the expert knowledge of the physician. At first, the economic relationship between patient and doctor was based on a personal agreement; state regulations were only involved later. In Roman times the relationship was affected indirectly by the state, mostly by the adoption of the Act on Hygiene and partly by various socialeconomic regulations. However, in the early Middle Ages, the charitable activities undertaken by the monastic population, with their limited medical knowledge, proved to be a backward step in the development of the healthcare system. It was not until the development of medical knowledge at the emerging universities, especially during the Renaissance, that regulations reentered healthcare and the better education of physicians marked the new era. During the investigated period (from the Enlightenment to the Second World War), the state, as a third party, was completely integrated in the system. Furthermore, in addition to the existing health services, health insurance was established, which marked the beginning of a healthcare system. This formed a solid foundation for the development of modern medicine and the regulation of the so-called welfare state. This article discusses the basic healthcare legislation in Slovenia during four different development periods; the Habsburg Monarchy, the Austro- Hungarian Monarchy, the State of Slovenes, Croats and Serbs, and the Kingdom of Yugoslavia. The development of the healthcare system during this sensitive era is clearly described; the changes in healthcare services are presented and healthcare insurance is analysed from a legal point of view. All of this led to the formation of the social healthcare policy, which signifies the existence of a modern state. The development of the health system in Slovenia was mainly influenced by two significant factors: firstly, by the reforms initiated by Empress Maria Theresa and her son Joseph II at the end of the 18th century and, secondly, by the establishment of insurance some one hundred years later.